2017
DOI: 10.1080/17425247.2017.1289174
|View full text |Cite
|
Sign up to set email alerts
|

Patient evaluation of the redesigned follitropin alfa pen injector

Abstract: This study demonstrated that both IVF/ART-experienced and -naïve women with infertility found the redesigned pen injector easy to learn to use and to use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…The findings reported in this study are consistent with previous studies regarding the evaluation of the GONAL-f pen injector by women with recent or current infertility requiring ART or IVF and fertility nurses [4,5,19]. In a previous study, IVF/ART-experienced andnaïve women with infertility found the redesigned pen injector 'easy to learn to use' and 'easy to use' [5]. Fertility nurses rated the redesigned pen injector as 'easy to learn and use' and 'easier to teach' than expected [4].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings reported in this study are consistent with previous studies regarding the evaluation of the GONAL-f pen injector by women with recent or current infertility requiring ART or IVF and fertility nurses [4,5,19]. In a previous study, IVF/ART-experienced andnaïve women with infertility found the redesigned pen injector 'easy to learn to use' and 'easy to use' [5]. Fertility nurses rated the redesigned pen injector as 'easy to learn and use' and 'easier to teach' than expected [4].…”
Section: Discussionsupporting
confidence: 91%
“…The first GONAL-f pen injector was approved in Europe in 2011 and since then it has been redesigned based on feedback from human factors engineering evaluations to improve robustness, handling, and readability [3]. The redesigned GONAL-f pen injector was evaluated by women with recent or current infertility requiring ART or in-vitro fertilization (IVF) and fertility nurses, and the device was considered easy to use [4,5,6]. Furthermore, an estimated 16,525,975 treatment cycles have been conducted since GONAL-f r-hFSH first gained marketing authorization for the stimulation of multifollicular development in patients undergoing medically assisted reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these products have greater stability and liquid formulations of recombinant products have been produced, removing the need for reconstitution before injection. This in turn has enabled the development of pen injection devices, which are designed to improve ease-of-use and patient convenience, including the ability to both select the starting dose with greater precision (in increments as low as 12.5 IU) and adapt the dose during treatment, based on treatment response in small increments (12.5 IU) (142144).…”
Section: Injection Devicesmentioning
confidence: 99%
“…A novel liquid formulation of r-hFSH/r-hLH was developed that does not require reconstitution and can be delivered subcutaneously using a prefilled, multi-dose pen injector, similar to the one currently available for GONAL-f ® (follitropin alfa; Merck KGaA, Darmstadt, Germany) and Ovidrel ® (rhCG; Merck KGaA, Darmstadt, Germany). Studies of this pen injector have demonstrated that health-care professionals find the pen injector easy to teach to use and that both health-care professionals and patients find the pen injector easy to learn to use, and can use it safely and effectively ( 4 , 5 ). The pen injector provides reassurance that the correct dose has been administered, displaying feedback on the dose administered, and as there is no need for reconstitution, concern about correct preparation is reduced ( 4 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of this pen injector have demonstrated that health-care professionals find the pen injector easy to teach to use and that both health-care professionals and patients find the pen injector easy to learn to use, and can use it safely and effectively ( 4 , 5 ). The pen injector provides reassurance that the correct dose has been administered, displaying feedback on the dose administered, and as there is no need for reconstitution, concern about correct preparation is reduced ( 4 , 6 ). Furthermore, the pen injector has been demonstrated to reliably dispense accurate doses under a range of conditions, including cold, standard and warm atmospheres, and subsequent to freefall, vibration, dry-heat, cold-storage, and shipping preconditioning ( 7 ).…”
Section: Introductionmentioning
confidence: 99%